Genetic analysis of Hass avocado variants using SSRs and EST-SSRs - Guillén-Andrade, Héctor; Martinez, Elizabeth; Escalera-Ordaz, Ana Karen; Tapia Vargas, Luis Mario (Revista Mexicana de Ciencias Agrícolas, 2024)
The research was carried out at the Plant Genetic Resources Laboratory of the ‘Presidente Juárez’ Faculty of Agrobiology, Michoacán University of San Nicolás de Hidalgo, in 2020 and 2022. The objective was to determine the viability of molecular markers of the SSR and EST-SSR types and their usefulness for the discrimination of avocado variants of the Hass variety. For this purpose, seven variant genotypes of Hass avocado and the Hass variety were analyzed using 19 SSR markers and nine EST-SSR markers. The InfoGen 2016 program helped determine the polymorphism information content (PIC) and the following genetic parameters: genetic diversity (I), heterozygosity (He), and number of effective alleles (Na) per locus. Genetic distances were estimated using the Jaccard index criterion applying the Neighbor-joining hierarchical clustering method. The analysis determined a total of 757 bands, an average of 27.03 alleles/marker locus and an average PIC value of 28.61%. In terms of genetic parameters, the EM2HG genotype had the highest genetic diversity value (I= 0.47), a PIC of 0.36 and a Na= 1.92. The Hass variety and the EM6HG variant showed the greatest genetic similarity (43%). These results show the viability of SSR and EST-SSR markers for the discrimination of closely related Hass avocado genotypes.
Keywords: Persea americana; genetic diversity